Physical Activity Enhancement to a Behavioral Weight Loss Program for Severely Obese Individuals: A Preliminary Investigation. (14th October 2012) - Unick, Jessica L.; O'Leary, Kevin C.; Bond, Dale S.; Wing, Rena R.
Abstract : Severe obesity is characterized by low physical activity (PA) and interventions to enhance PA are needed. Participants (45.0 ± 3.9 kg/m 2 ) were randomized to a 6-month standard behavioral weight loss program (SBWL; n = 14) or SBWL+technology (SBWL+TECH; n = 15). Both groups received identical SBWL treatment and SBWL+TECH also received a wearable PA monitor, providing "real-time" feedback, and website access to monitor energy balance. 6-month retention was similar between groups (SBWL: 12/13 versus SBWL+TECH: 11/14 completers; P = 0.19) and adherence to wearing the armband was excellent (91.3% of days). Although differences in PA between groups did not meet conventional thresholds of significance, SBWL+TECH increased their moderate-to-vigorous intensity PA by 132.9 ± 216.8 min/week, which was 3 times greater than SBWL (44.8 ± 124.3 min/week; P = 0.27; Cohen's d = 0.50). There was a trend for SBWL+TECH to self-monitor for a greater proportion of days compared to SBWL (86.2 ± 21.4% versus 71.5 ± 19.4%; P = 0.098; Cohen's d = 0.72). The difference in weight loss between groups was modest (SBWL+TECH: −10.0 ± 7.1% versus SBWL: −7.8 ± 6.7%; P = 0.46). These preliminary findings suggest that PA monitors may be one strategy for increasing PA among the severely obese. Larger, long-term trials are needed.